STUDI AKTIVITAS DIURNAL SIAMANG (SYMPHALANGUS SYNDACTYLUS) DI KEBUN BINATANG TAMAN RIMBO PROVINSI JAMBI - Yola Yolanda; Bakti Mandala; Citra Rahmatia (LPPM Universitas Muhammadiyah Jambi, 2026)
Siamang is a protected species based on the Minister of Environment and Forestry Regulation No. P.106 of 2018. As an endangered species.The activities observed were agonistic activity (AG), defecation activity (DF), grooming activity (GR), resting activity (IS), drinking activity (MI), eating activity (MK), moving activity (MO), vocal activity (VC). As well as urination activity (UR). This research aims to determine and study the daily behavior of Siamang. The results obtained from research regarding the diurnal activity of Siamang in KBTR Jambi Province for 10 days (360,000 seconds), namely the average activity from highest to lowest is move activity 278,106 seconds; 77.25%, rest activity 36,535 seconds; 10.14%, vocalization activity 32,311 seconds; 8.97%, grooming activity 6,398 seconds; 1.77%, agonistic activity 3,196 seconds; 0.88%, eating activity 2,080; 0.57%, drinking activity 715 seconds; 0.19%, urination activity 409 seconds; 0.11%, defecation activity 250 seconds; 0.06%. The highest activity pattern carried out by gibbons during the day is moving activity and the lowest is defecation activity. The movement activity of the gibbon during the day is 278,106 seconds; 77.25%. The highest movement activity results during the day are because gibbons are animals that are active during the day.